2020
DOI: 10.1080/21556660.2020.1797753
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of oxycodone by mouth in coronary artery bypass surgery patients – a randomized trial

Abstract: Objective: Pain after coronary artery bypass (CAB) surgery is severe. Analgesic administration by mouth is unreliable until after gastrointestinal function has recovered. We evaluated the bioavailability of oxycodone co-administered with naloxone by mouth in patients after CAB surgery using either a conventional extracorporeal circulation (CECC) or off-pump surgery (OPCAB). Methods: Twenty-four patients, 50-73 years, 12 with CECC and 12 with OPCAB, were administered a 10/5 mg oxycodone-naloxone controlled-rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Absorption of nasogastric elixir paracetamol in adults undergoing cardiac surgery was delayed compared with healthy adults [ 42 ]. The absorption of oral oxycodone is also delayed after cardiac surgery, with the most profound delay (when compared with preoperative administration) observed on the first postoperative day [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of nasogastric elixir paracetamol in adults undergoing cardiac surgery was delayed compared with healthy adults [ 42 ]. The absorption of oral oxycodone is also delayed after cardiac surgery, with the most profound delay (when compared with preoperative administration) observed on the first postoperative day [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This semi-synthetic opioid is stronger than morphine [40]. It is absorbed mainly in the small intestine [41]. Szałek et al, conducted a study on the pharmacokinetics of oxycodone in patients after total gastrectomy.…”
Section: Analgesic Drugsmentioning
confidence: 99%
“…Chemically, oxycodone is a weak base with a p K a value of 8.53 7 . It is moderately protein bound in plasma (38‐45%) and has oral bioavailability of 40‐70% 8–11 . Previously, Seaton et al 12 found oxycodone to be excreted into human breast milk during the first 72 h after Caesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is moderately protein bound in plasma (38-45%) and has oral bioavailability of 40-70%. [8][9][10][11] Previously, Seaton et al 12 found oxycodone to be excreted into human breast milk during the first 72 h after Caesarean delivery. The highest oxycodone concentrations in breast milk were >100 ng/mL and neonatal exposure was up to 10% of a therapeutic infant dose through ingestion.…”
mentioning
confidence: 99%